The Concept of International Treaties and Their Role in Conflict Resolution - شكر, احمد فرج (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
International treaties are considered one of the fundamental tools of international law to regulate relations among states and to settle disputes arising between them. This research aims to examine the concept and types of international treaties, focusing on their effective role in resolving international conflicts during the period (2003–2023). The study adopts a descriptive-analytical approach through the analysis of legal texts and relevant academic studies. The research concludes that international treaties have played a significant role in reducing international disputes; however, their effectiveness has often been limited due to political interests and weak enforcement mechanisms.